(untitled) (Antropolítica - Revista Contemporânea de Antropologia, 2024)
Boys love (BL) names a set of literary and audiovisual productions of male homoeroticism. Since the emergence of this genre (initially as fan texts and then as television series) there have been intense and tumultuous debates about the representation of gay men and consumption practices considered fetishistic and hypersexualizing. In the case of the Brazilian BL fandom, through the digital ethnographic method, with systematic and individual participant observation among fans, I will show that surveillance of other people’s consumption has become intrinsic to the consumption of BL series itself, a phenomenon that I call moral consumption, which involves other relations of distinction, specifically between fujoshi and non-fujoshi Brazilian fans. This differentiation produces a symbolic reductionism that is intrinsically associated with orientalist discourses and practices, which I name fujoshi fetishism, another concept that I will address in this article.